State spaces of resistance: industrial tree plantations and the struggle for land in Laos - Miles, K.-L.; Suhardiman, Diana; Dwyer, M.B. (Wiley, 2018)
Land grabbing has transformed rural environments across the global South, generating resistance or political reactions “from below”. In authoritarian countries like Laos, where resource investments are coercively developed and insulated from political dissent, resistance appears absent at first glance. Yet, it is occurring under the radar, largely outside transnational activist networks. In this article, we examine how resistance can protect access to rural lands in contexts where it is heavily repressed. Resistance here occurs with, rather than against the state by foregrounding the contradictions of land use and ownership within state spaces, such as competing goals of large-scale industrial plantations versus smallholder agriculture and national forest conservation. Such contradictions are engaged by using historical, place-based political connections to exploit the scalar frictions of a fragmented state and occupying plantation clearance sites to highlight contested lands in situ. Nonetheless, such strategies remain spatially and socially uneven amongst the Lao peasantry.